The Effectiveness Of Collaborative Learning Method For Teaching Writing To Tenth Grade Students Of SMA Muhammadiyah 1 Surakarta In 2015/2016 Academic Year - Mutriyanti, Anik, Dr. Anam Sutopo, S.Pd., M.Hum (2016)
ABSTRACTS Anik Mutdriyanti. A320120145. THE EFFECTIVENESS OF COLLABORATIVE LEARNING METHOD FOR TEACHING WRITING TO TENTH GRADE STUDENTS OF SMA MUHAMMADIYAH 1 SURAKARTA IN 2015/2016 ACADEMIC YEAR. Research Paper. School of Teacher Training and Education, Muhammadiyah University of Surakarta. October 2016. This research aims to describe the implementation of collaborative learning method for teaching writing to tenth grade students of SMA Muhammadiyah 1 Surakarta in 2015/2016 academic years. The objectives of the research are to know the process of the implementation of collaborative learning method for teaching writing, to know the effectiveness of collaborative learning method for teaching writing, and to know the advantages and disadvantages of teaching writing using collaborative learning method. The subject of the research focuses on tenth grade students that consist of 42 students. The techniques of collecting data are observation, interview, document, and test. In analyzing the data the researcher uses descriptive analysis that takes following steps: identifying the collected data, analyzing the data based on the problem statement, and drawing conclusion. Based on the research finding, the researcher concludes the findings based on the investigation and discussion of findings. First, the implementation of collaborative learning is applied by the teacher by three steps: opening, main activity, and closing. Second, the effectiveness of collaborative learning is measured by the test given to students. The students' mean scores of pre-test is 45,00. It is categorized as a poor score. Then the students' mean score of post-test is 86,31 that categorized as an excellent score. It can be said that collaborative learning is effective to be implemented for teaching writing with the improvement of scores 41,31. Then the advantages of and disadvantages of collaborative learning can be known by observing and questionnaire. The advantages of collaborative learning are that learning is more enjoyable and students are practiced to be good at teamwork. Meanwhile the disadvantages of collaborative learning are the lack of time and less contribution of students in a group. Keywords: teaching writing, collaborative learning